Gobernanza y Gobernabilidad para el Desarrollo Territorial en el Cantón Sigchos. - García Sánchez, Ana Lucia (2020)
model of governability for sustainable territorial development must be anchored in the institutional strengthening and the capabilities of the human talent of local governments. These must give support to the Government in its management, to satisfy the demand of the citizens and legitimize its leadership in the full exercise of a democratic mandate, and in this way to lead the public policies to improve the quality of life of the inhabitants of the territory.